COVID-19 Vaccination Acceptance Among Healthcare Workers and Non-healthcare Workers in China: A Survey - Wang, Ming-Wei; Wen, Wen; Wang, Nan; Zhou, Meng-Yun; Wang, Chun-yi; Ni, Jie; Jiang, Jing-jie; Zhang, Xing-wei; Feng, Zhan-Hui; Cheng, Yong-Ran (Frontiers in Public Health, 2021)
Background： The coronavirus pneumonia is still spreading around the world. Much progress has been made in vaccine development, and vaccination will become an inevitable trend in the fight against this pandemic. However, the public acceptance of COVID-19 vaccination still remains uncertain. Methods：An anonymous questionnaire was used in Wen Juan Xing survey platform. All the respondents were divided into healthcare workers and nonhealthcare workers. Multinomial logistic regression analyses were performed to identify the key sociodemographic, cognitive, and attitude associations among the samples of healthcare workers and nonhealthcare workers. Results: A total of 2580 respondents completed the questionnaire, including 1,329 healthcare workers and 1,251 nonhealthcare workers. This study showed that 76.98% of healthcare workers accepted the COVID-19 vaccine, 18.28% workers were hesitant, and 4.74% workers were resistant. Among the nonhealthcare workers, 56.19% workers received the COVID-19 vaccine, 37.57% workers were hesitant, and 6.24% workers were resistant. Among the healthcare workers, compared with vaccine recipients, vaccine-hesitant individuals were more likely to be female (AOR = 1.52, 95% CI: 1.12–2.07); vaccine-resistant individuals were more likely to live in the suburbs (AOR = 2.81, 95% CI: 1.44–3.99) with an income of 10,000 RMB or greater (AOR = 2.00, 95% CI: 1.03–3.90). Among the nonhealthcare workers, vaccine-hesitant individuals were more likely to be female (AOR = 1.66, 95% CI: 1.31–2.11); vaccine-resistant individuals were also more likely to be female (AOR = 1.87, 95% CI: 1.16–3.02) and older than 65 years (AOR = 4.96, 95% CI: 1.40–7.62). There are great differences between healthcare workers and nonhealthcare workers in their cognition and attitude towards vaccines. Conclusions: Our study shows that healthcare workers are more willing to be vaccinated than nonhealthcare workers. Current vaccine safety issues continue to be a major factor affecting public acceptance, and to expand vaccine coverage in response to the COVID-19 pandemic, appropriate vaccination strategies and immunization programs are essential, especially for nonhealthcare workers.